A secondary battery and device thereof

By using the first and second positive electrode active substances with different working voltage platforms in the positive electrode sheet of the lithium-ion battery, the complementarity and synergistic effect of the charging and discharge platform is achieved, and the performance of the lithium-ion battery in the low temperature and low SOC state is solved. Problem, significantly improving power performance and energy efficiency.

CN111446488BActive Publication Date: 2025-02-18CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202010365063.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-04-30
Publication Date
2025-02-18
Estimated Expiration
2040-04-30

AI Technical Summary

Technical Problem

Existing lithium-ion batteries show problems such as degraded power performance, low energy efficiency, and poor capacity retention rate in low temperature and low SOC states.

Method used

A secondary battery is designed, and its positive electrode sheet contains the first positive electrode active substance and the second positive electrode active substance with different working voltage platforms. Through the charging and discharging platforms of the two, synergistic effects are achieved, and ions and electron conduction are optimized. performance.

Benefits of technology

It significantly improves the key performance of secondary batteries in low temperature and low SOC states, such as power performance, energy efficiency, capacity retention, etc.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN111446488B_ABST
    Figure CN111446488B_ABST
Patent Text Reader

Abstract

The present application relates to a secondary battery and a device thereof. The secondary battery of the present application comprises a positive electrode plate, wherein the positive electrode plate comprises a positive electrode current collector and a positive electrode active material layer, wherein the positive electrode active material layer is located on the surface of the positive electrode current collector, wherein the positive electrode active material layer comprises a first positive electrode active material and a second positive electrode active material having different working voltage platforms; and the lithium ion solid phase diffusion coefficient of the positive electrode plate is 10 ‑17 cm 2 ·s ‑1 ~10 ‑5 cm 2 ·s ‑1 , the resistance of the positive electrode sheet is 0.05Ω to 2Ω. The power performance of the secondary battery provided in the present application is significantly improved under low temperature, especially under low temperature and low SOC conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of batteries, and in particular, to a secondary battery and a device thereof. Background Art

[0002] Lithium-ion batteries are widely used in electric vehicles and consumer electronics due to their high energy density, high output power, long cycle life and low environmental pollution. Electric vehicles have high power requirements for the driving power supply during driving, so lithium-ion batteries are also required to have better power characteristics.

[0003] Temperature is one of the environmental factors that has the greatest impact on the battery's charge and discharge performance. In a low-temperature environment, the power performance of lithium-ion batteries decreases. In addition, the battery state of charge (SOC) reflects the ratio of the battery's remaining capacity to the battery capacity. In a low SOC state, the power performance of lithium-ion batteries is often also affected. Therefore, existing lithium-ion batteries perform poorly in key performance aspects such as power at low temperatures and low SOC, operating energy efficiency, low-temperature capacity, and energy retention rate.

[0004] In order to overcome the shortcomings of the prior art, this application is proposed. Summary of the invention

[0005] In view of this, embodiments of the present application provide a secondary battery and a device thereof.

[0006] In a first aspect, the present application provides a secondary battery, comprising a positive electrode plate, wherein the positive electrode plate comprises a positive electrode current collector and a positive electrode active material layer, wherein the positive electrode active material layer is located on the surface of the positive electrode current collector, wherein the positive electrode active material layer comprises a first positive electrode active material and a second positive electrode active material having different operating voltage platforms; the lithium ion solid phase diffusion coefficient of the positive electrode plate is 10 -17 cm 2 ·s -1 ~10 -5 cm 2 ·s -1 , preferably 10 -13 cm 2 ·s -1 ~10 -9 cm 2 ·s -1 ; The resistance of the positive electrode plate is 0.05Ω~2Ω, preferably 0.1Ω~1.5Ω.

[0007] In a second aspect, the present application provides a device, which includes the secondary battery in the first aspect of the present application, and the secondary battery can be used as a power source for the device, and can also be used as an energy storage unit for the device.

[0008] Compared with the prior art, the technical solution of the present application has at least the following beneficial effects.

[0009] The secondary battery provided by the present application includes a first positive electrode active material and a second positive electrode active material with different working voltage platforms in the positive electrode active material layer of the positive electrode plate. The charging and discharging platforms of the two positive electrode active materials are complementary and synergistic. By achieving a better match between the ion conductivity and the electronic conductivity of the plate, the lithium ion solid phase diffusion coefficient and resistance of the positive electrode plate are both within a better range. Therefore, the key performances of the secondary battery including the positive electrode plate at low temperature, especially at low temperature and low SOC, such as power, operating condition energy efficiency, low temperature capacity and energy retention rate, are significantly improved.

[0010] The device of the present application includes the secondary battery provided by the present application, and thus has at least the same advantages as the secondary battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] The secondary battery and device of the present application are described in detail below in conjunction with the accompanying drawings and specific embodiments.

[0012] Figure 1 is a perspective view of a secondary battery according to a specific embodiment of the present application as a lithium ion secondary battery;

[0013] Figure 2 yes Figure 1 An exploded view of a lithium-ion secondary battery is shown;

[0014] Figure 3 is a three-dimensional diagram of a battery module according to a specific embodiment of the present application;

[0015] Figure 4 is a three-dimensional diagram of a battery pack according to a specific embodiment of the present application;

[0016] Figure 5 yes Figure 4 An exploded view of the battery pack shown;

[0017] Figure 6 is a schematic diagram of a device according to a specific embodiment of the present application;

[0018] The reference numerals are described as follows:

[0019] 1 battery pack;

[0020] 2 upper box;

[0021] 3 lower box;

[0022] 4 battery modules;

[0023] 5. Secondary battery;

[0024] 51 outer packaging;

[0025] 52 electrode assembly;

[0026] 53 Top cover assembly. DETAILED DESCRIPTION

[0027] The present application is further described below in conjunction with specific implementations. It should be understood that these specific implementations are only used to illustrate the present application and are not used to limit the scope of the present application.

[0028] Secondary battery

[0029] The present application provides a secondary battery, wherein the positive electrode plate comprises a positive electrode current collector and a positive electrode active material layer, wherein the positive electrode active material layer is located on the surface of the positive electrode current collector, wherein the positive electrode active material layer comprises a first positive electrode active material and a second positive electrode active material having different working voltage platforms, and the lithium ion solid phase diffusion coefficient of the positive electrode plate is 10 -17 cm 2 ·s -1 ~10 -5 cm 2 ·s -1 , preferably 10 -13 cm 2 ·s -1 ~10 -9 cm 2 ·s -1 The resistance of the positive electrode plate is 0.05Ω~2Ω, preferably 0.1Ω~1.5Ω, and more preferably 0.2Ω~1Ω.

[0030] The lithium ion solid phase diffusion coefficient of the positive electrode plate characterizes the diffusion and mass transfer rate of lithium ions in the plate, specifically refers to the amount of lithium ion substances that vertically pass through the plate per unit area in a unit time under unit concentration gradient conditions in the porous electrode. The resistance of the positive electrode plate reflects the electronic conductivity of the plate. If the resistance value of the plate is small, the electronic conductivity of the plate is good, the ohmic polarization is small, and the discharge platform is high at low temperature. In the embodiment of the present application, a first positive electrode active material and a second positive electrode active material with different working voltage platforms are used in the positive electrode plate of the secondary battery. Through the complementarity of the charge and discharge platforms of the two positive electrode active materials, a synergistic effect occurs, so that the lithium ion solid phase diffusion coefficient and resistance of the positive electrode plate are both within a better range, that is, the ion conductivity and electronic conductivity of the plate are better matched. Therefore, the key performances of the secondary battery containing the plate at low temperature, especially at low temperature and low SOC, such as power, operating condition energy efficiency, low temperature capacity and energy retention rate are significantly improved.

[0031] The first positive electrode active material described in the present application can be selected from layered lithium nickel transition metal oxides.

[0032] In some embodiments of the present application, the layered lithium nickel transition metal oxide as the first positive electrode active material is selected from: Li x1 Ni (1-y1-z1-a1) Co y1 Mn z1 M1 a1 O2、Li x2 Ni (1-y2-z2-a2) Co y2 Al z2 M2 a2 O2, and one or more of the composite materials obtained by coating and modification of the above materials; wherein, 0.90≤x1≤1.05, 0<y1≤0.2, 0<z1≤0.2, 0≤a1≤0.05, M1 is selected from one or more of Ti, Al, Zr, Mg, Zn, Ba, Mo, and B; 0.90≤x2≤1.05, 0<y2≤0.1, 0<z2≤0.1, 0≤a2≤0.05, M2 is selected from one or more of Ti, Mn, Zr, Mg, Zn, Ba, Mo, and B.

[0033] In some embodiments of the present application, the layered lithium nickel transition metal oxide as the first positive electrode active material is preferably selected from: Li x1 Ni (1-y1-z1-a1) Co y1 Mn z1 M1 a1 O2、Li x2 Ni (1-y2-z2-a2) Co y2 Al z2 M2 a2 O2, and one or more of the composite materials obtained by coating and modification of the above materials; wherein 0<y1+z1+a1≤0.4; 0<y2+z2+a2≤0.4.

[0034] Specifically, the layered lithium nickel transition metal oxides described in this application include but are not limited to LiNi 0.5 Co 0.2 Mn0 .3 O2、LiNi 0.5 Co 0.25 Mn 0.25 O2、LiNi 0.55 Co 0.15 Mn 0.3 O2、LiNi 0.55 Co 0.1 Mn 0.35 O2、LiNi 0.55 Co 0.05 Mn 0.4 O2、LiNi 0.6 Co0.2 Mn 0.2 O2、LiNi 0.65 Co 0.15 Mn 0.2 O2、LiNi 0.65 Co 0.12 Mn 0.23 O2、LiNi 0.65 Co 0.1 Mn 0.25 O2、LiNi 0.65 Co 0.05 Mn 0.3 O2、LiNi 0.7 Co 0.1 Mn 0.2 O2、LiNi 0.75 Co 0.1 Mn 0.15 O2、LiNi 0.8 Co 0.1 Mn 0.1 O2、LiNi 0.85 Co 0.05 Mn 0.1 O2、LiNi 0.88 Co 0.05 Mn 0.07 O2、LiNi 0.9 Co 0.05 Mn 0.05 O2、LiNi 0.92 Co 0.03 Mn 0.05 O2、LiNi 0.95 Co 0.02 Mn 0.03 O2, etc., or it can be a substance after the above substances are partially replaced and modified by doping elements M1 or M2, wherein M1 is selected from one or more of Ti, Al, Zr, Mg, Zn, Ba, Mo, and B, and M2 is selected from one or more of Ti, Mn, Zr, Mg, Zn, Ba, Mo, and B.

[0035] The second positive electrode active material described in the present application is selected from olivine-type lithium-containing phosphates.

[0036] In some embodiments of the present application, the olivine-type lithium-containing phosphate as the second positive electrode active material is LiFe 1-x3-y3 Mn x3 M' y3 PO4, wherein 0≤x3≤1, 0≤y3≤0.1, 0≤x3+y3≤1, and M' is selected from one or more of transition metal elements and non-transition metal elements except Fe and Mn.

[0037] In some other embodiments of the present application, the olivine-type lithium-containing phosphate as the second positive electrode active material is preferably a doped and modified LiFePO4, LiMnPO4, LiMn 1-x4 Fe x4 One or more of PO4, where 0<x4<1.

[0038] Furthermore, the present application also makes the complementary effect of the charge and discharge platform of the two positive electrode active materials more prominent by matching the lithium ion solid phase diffusion coefficient and powder resistivity range of the first positive electrode active material and the second positive electrode active material, and makes the ion conductivity and the electronic conductivity of the positive electrode sheet better matched, thereby more significantly improving the power performance of the battery cell at low temperature and low SOC. Based on this, some optional implementations provided by the present application are as follows:

[0039] In some embodiments of the present application, the lithium ion solid phase diffusion coefficient of the first positive electrode active material is 10 - 13 cm 2 ·s -1 ~10 -7 cm 2 ·s -1 In some other embodiments of the present application, the lithium ion solid phase diffusion coefficient of the first positive electrode active material is preferably 10 -11 cm 2 ·s -1 ~10 -9 cm 2 ·s -1 .

[0040] In some embodiments of the present application, the powder resistivity of the first positive electrode active material at 20 MPa is 1000Ω·cm~20000Ω·cm; in some embodiments of the present application, the powder resistivity of the first positive electrode active material at 20 MPa is preferably 2000Ω·cm~10000Ω·cm; in other embodiments of the present application, the powder resistivity of the first positive electrode active material at 20 MPa is more preferably 3000Ω·cm~6000Ω·cm.

[0041] In some embodiments of the present application, the lithium ion solid phase diffusion coefficient of the second positive electrode active material is 10 - 17 cm 2 ·s -1 ~10 -11 cm 2 ·s -1 In some embodiments of the present application, the lithium ion solid phase diffusion coefficient of the second positive electrode active material is preferably 10-16 cm 2 ·s -1 ~10 -13 cm 2 ·s -1 In some other embodiments of the present application, the lithium ion solid phase diffusion coefficient of the second positive electrode active material is more preferably 10 -15 cm 2 ·s -1 ~10 -14 cm 2 ·s -1 .

[0042] In some embodiments of the present application, the powder resistivity of the second positive electrode active material at 20 MPa is 10Ω·cm~4000Ω·cm; in some embodiments of the present application, the powder resistivity of the second positive electrode active material at 20 MPa is preferably 20Ω·cm~800Ω·cm; in other embodiments of the present application, the powder resistivity of the second positive electrode active material at 20 MPa is more preferably 200Ω·cm~550Ω·cm.

[0043] In some embodiments of the present application, the molar percentage content of the second positive electrode active material in the positive electrode active material is 0.5% to 50%; in some embodiments of the present application, the molar percentage content of the second positive electrode active material in the positive electrode active material is preferably 0.6% to 30%; in other embodiments of the present application, the molar percentage content of the second positive electrode active material in the positive electrode active material is more preferably 0.7% to 20%.

[0044] Furthermore, the present application proposes a preferred scheme for the particle morphology of the first positive electrode active material. In some embodiments of the present application, the particle morphology of the first positive electrode active material is single crystal particles, polycrystalline particles, or a mixture of single crystal particles and a small amount of polycrystalline particles; single crystal particles are preferred. Single crystal particles refer to a crystal whose entirety is composed of the same spatial lattice in the three-dimensional direction. Since single crystal particles have the characteristics of fewer interfaces, lower specific surface area, and higher mechanical strength compared to polycrystalline particles, it is not easy for particles to break during processing and use. Especially when used under high voltage, single crystal particles have fewer side reactions and higher chemical stability.

[0045] Furthermore, the present application also proposes a preferred scheme for the average particle size of the second positive electrode active material. In some embodiments of the present application, the average particle size Dv50 of the second positive electrode active material is 1 μm to 15 μm; in some embodiments of the present application, the average particle size Dv50 of the second positive electrode active material is preferably 4.5 μm to 10 μm; in other embodiments of the present application, the average particle size Dv50 of the second positive electrode active material is more preferably 5 μm to 9 μm.

[0046] In a preferred embodiment of the present application, a first positive electrode active material (ternary positive electrode material single crystal particles) with a smaller average particle size is mixed with a second positive electrode active material (lithium iron phosphate secondary particles) with a larger average particle size as the positive electrode active material of the electrode of the present application, which is beneficial to improving the compaction density of the electrode, thereby improving the energy density of the battery cell.

[0047] Furthermore, in some embodiments of the present application, I003 / I110 in the X-ray diffraction spectrum of the first positive electrode active material is 2 to 20; in some embodiments of the present application, I003 / I110 in the X-ray diffraction spectrum of the first positive electrode active material is preferably 4 to 15; in other embodiments of the present application, I003 / I110 in the X-ray diffraction spectrum of the first positive electrode active material is more preferably 6 to 10.

[0048] In some embodiments of the present application, the lattice parameter c / a in the X-ray diffraction pattern of the first positive electrode active material is 2-7; in some embodiments of the present application, the lattice parameter c / a in the X-ray diffraction pattern of the first positive electrode active material is preferably 3-6.

[0049] As described above, the present application proposes a preferred scheme of I003 / I110 and lattice parameter c / a in the X-ray diffraction spectrum of the first positive active material. Among them, I003 / I110 in the X-ray diffraction spectrum of the first positive active material is the diffraction peak intensity ratio of the (003) crystal plane to the (110) crystal plane on the XRD diffraction spectrum of the first positive active material, which reflects the number, length and diffusion speed of the lithium ion diffusion path, and is a characteristic of the ion transmission kinetics. Generally speaking, the smaller I003 / I110 is, the better the kinetics of lithium ion transmission is. The lattice parameter c / a in the X-ray diffraction spectrum of the first positive active material is the ratio of the lattice parameter c-axis to the a-axis in the crystal structure of the smallest component unit (i.e., an independent lattice) in the X-ray diffraction spectrum of the first positive active material. The c-axis reflects the size of the lithium ion diffusion channel, and the a-axis reflects the length of the lithium ion diffusion path. The larger the c / a, the larger the diffusion channel, the shorter the diffusion path, and the faster the lithium ion diffusion transmission. The present application optimizes the I003 / I110 and lattice parameter c / a in the X-ray diffraction spectrum of the first positive electrode active material to make the ion conductivity of the first positive electrode active material within a better range, thereby promoting the matching of the ion conductivity and the electronic conductivity of the electrode sheet.

[0050] Further, in some embodiments of the present application, the mass percentage of the carbon coating of the second positive electrode active material is 0.1% to 5%, preferably 0.5% to 3%, and more preferably 1% to 2%. Within the above range, the powder resistivity of the second positive electrode active material is low, the conductivity is good, and it has good interface stability.

[0051] In some embodiments of the present application, the positive electrode sheet provided satisfies: 0.41<(R d +R ct ) / R cat <0.99, and 0.2<R ct / R d <2; where R cat is the total impedance of the positive electrode, R d is the lithium ion diffusion impedance of the positive electrode plate, R ct is the charge transfer impedance of the positive electrode. Under the above conditions, the ionic conductivity and electronic conductivity of the positive electrode are optimally matched.

[0052] As described above, the present application achieves a better match between the ionic conductivity and electronic conductivity of the positive electrode plate using the mixed positive electrode active material by mixing two positive electrode active materials with different operating voltage platforms in a certain ratio, and optimizing the material type, lithium ion solid phase diffusion coefficient, powder resistivity, particle morphology, particle size and carbon coating amount, and specific parameters in the X-ray diffraction spectrum of the two positive electrode active materials. Therefore, the key performance of the secondary battery containing the positive electrode plate at low temperature, especially at low temperature and low SOC, such as power, operating energy efficiency, low temperature capacity and energy retention rate, is significantly improved.

[0053] In addition, the positive electrode sheet of the present application may also include a conductive agent and a binder, wherein the type and content of the conductive agent and the binder are not specifically limited and can be selected according to actual needs. The binder generally includes a fluorinated polyolefin binder. Relative to the fluorinated polyolefin binder, water is generally a good solvent, that is, the fluorinated polyolefin binder generally has good solubility in water. For example, the fluorinated polyolefin binder may include but is not limited to polyvinylidene fluoride (PVDF), vinylidene fluoride copolymers or their modified (for example, carboxylic acid, acrylic acid, acrylonitrile, etc.) derivatives. In the positive electrode material layer, the mass percentage content of the binder may be due to the poor conductivity of the binder itself, so the amount of the binder cannot be too high. Preferably, the mass percentage content of the binder in the positive electrode active material layer is less than or equal to 2wt% to obtain a lower pole sheet impedance. The conductive agent of the positive electrode sheet may be a variety of conductive agents suitable for lithium ion (secondary) batteries in the art, for example, may be a combination of one or more of acetylene black, conductive carbon black, carbon fiber (VGCF), carbon nanotubes (CNT), Ketjen black, etc.

[0054] In the positive electrode sheet of the present application, the type of positive electrode current collector is not specifically limited and can be selected according to actual needs. The positive electrode current collector can usually be a layer body, the positive electrode current collector can usually be a structure or part that can collect current, and the positive electrode current collector can be various materials in the art suitable for use as a positive electrode current collector for an electrochemical energy storage device. For example, the positive electrode current collector can include but is not limited to metal foil, and more specifically can include but is not limited to nickel foil and aluminum foil.

[0055] The preparation method of the positive electrode sheet of the present application is as follows:

[0056] The first positive electrode active material and the second positive electrode active material are mixed in a solvent according to a molar percentage ratio, and a conductive agent and a binder are added to obtain a mixed slurry with a viscosity of 3000mPa·s to 20000mPa·s. The mixed slurry is allowed to stand for 24 to 48 hours to obtain a positive electrode active material slurry that does not gel, stratify, or settle. The slurry is coated on the electrode collector (or pre-coated on the bottom coating of the electrode collector), then dried, and finally the desired positive electrode sheet can be prepared by post-processing and welding the electrical connection components. In some embodiments, the electrical connection components can also be formed on the collector first and then the positive active material layer is formed.

[0057] Among them, the solvent used to mix the first positive electrode active material and the second positive electrode active material can be one or more of water, N-dimethylpyrrolidone (NMP), N-dimethylformamide (DMF), dimethyl sulfoxide (DMSO), ethanol, propylene glycol, etc., and the viscosity of the obtained mixed slurry is 3000mPa·s~20000mPa·s.

[0058] The viscosity of the mixed slurry can be measured by a viscometer. Equipment model: Brookfield DV2TLV, reference standard GB / T 10247-2008 "Viscosity Measurement Method". Under certain temperature and humidity, when a specific model of rotor rotates continuously at a constant speed in the sample, the shear force it receives causes the spring to generate torque, which is proportional to the viscosity, and the viscosity value is obtained.

[0059] Figure 1 A perspective view of a secondary battery according to a specific embodiment of the present invention as a lithium ion secondary battery is shown, Figure 2 yes Figure 1 An exploded view of a lithium-ion secondary battery is shown. Figure 1 and Figure 2 According to the present application, the lithium-ion secondary battery 5 (hereinafter referred to as the battery cell 5) includes an outer package 51, an electrode assembly 52, a top cover assembly 53 and an electrolyte (not shown). The electrode assembly 52 is contained in the outer package 51, and the number of the electrode assembly 52 is not limited, and can be one or more.

[0060] It should be noted that Figure 1 The battery cell 5 shown is a can-type battery, but the present application is not limited thereto. The battery cell 5 may be a pouch-type battery, that is, the housing 51 is replaced by a metal plastic film and the top cover assembly 53 is eliminated.

[0061] Except for using the positive electrode sheet containing the first positive electrode active material and the second positive electrode active material, the structure and preparation method of the secondary battery of the present application are well known per se.

[0062] In the lithium-ion secondary battery of the present application, the negative electrode plate generally includes a negative electrode current collector and a negative electrode active material layer located on the surface of the negative electrode current collector, and the negative electrode active material layer generally includes a negative electrode active material. The negative electrode active material can be various materials suitable for negative electrode active materials of electrochemical energy storage devices in the art, for example, it can be a combination of one or more of graphite, soft carbon, hard carbon, carbon fiber, mesophase carbon microspheres, silicon-based materials, tin-based materials, lithium titanate or other metals that can form alloys with lithium. Among them, the graphite can be selected from a combination of one or more of artificial graphite, natural graphite and modified graphite; the silicon-based material can be selected from a combination of one or more of elemental silicon, silicon oxide compounds, silicon-carbon composites, and silicon alloys; the tin-based material can be selected from a combination of one or more of elemental tin, tin oxide compounds, and tin alloys. The negative electrode current collector is generally a structure or part for collecting current, and the negative electrode current collector can be various materials suitable for use as negative electrode current collectors of electrochemical energy storage devices in the art, for example, the negative electrode current collector can be a metal foil, more specifically, a copper foil. In addition, the negative electrode plate can also be a lithium sheet.

[0063] In the lithium-ion secondary battery of the present application, the specific types and compositions of the isolation membrane and the electrolyte are not subject to specific restrictions and can be selected according to actual needs. Specifically, the isolation membrane can be selected from polyethylene films, polypropylene films, polyvinylidene fluoride films and their multilayer composite films. When the battery is a lithium-ion battery, a non-aqueous electrolyte is usually used as the electrolyte. As a non-aqueous electrolyte, a lithium salt solution dissolved in an organic solvent is usually used. Lithium salts are, for example, inorganic lithium salts such as LiClO4, LiPF6, LiBF4, LiAsF6, LiSbF6, or LiCF3SO3, LiCF3CO2, Li2C2F4(SO3)2, LiN(CF3SO2)2, LiC(CF3SO2)3, LiC n F 2n+1SO3 (n ≥ 2) and other organic lithium salts. The organic solvent used in the non-aqueous electrolyte is, for example, cyclic carbonates such as ethylene carbonate, propylene carbonate, butylene carbonate, and vinylene carbonate, chain carbonates such as dimethyl carbonate, diethyl carbonate, and methyl ethyl carbonate, chain esters such as methyl propionate, cyclic esters such as γ-butyrolactone, chain ethers such as dimethoxyethane, diethyl ether, diethylene glycol dimethyl ether, and triethylene glycol dimethyl ether, cyclic ethers such as tetrahydrofuran and 2-methyltetrahydrofuran, nitriles such as acetonitrile and propionitrile, or a mixture of these solvents.

[0064] In some embodiments, the lithium-ion secondary batteries may be assembled into a battery module. The battery module may contain a plurality of lithium-ion secondary batteries, and the specific number may be adjusted according to the application and capacity of the battery module. Figure 3 4 is an example of a battery module. Figure 3 In the battery module 4, the plurality of lithium-ion secondary batteries 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. The plurality of lithium-ion secondary batteries 5 may further be fixed by fasteners. Optionally, the battery module 4 may further include a housing having a storage space, and the plurality of lithium-ion secondary batteries 5 are stored in the storage space.

[0065] In some embodiments, the battery modules described above may also be assembled into a battery pack, and the number of battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack. Figure 4 and Figure 5 1 is a battery pack 1 as an example. Figure 4 and Figure 5 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.

[0066] Device

[0067] The second aspect of the present application provides a device, comprising the secondary battery described in the first aspect of the present application, wherein the secondary battery can be used as a power source of the device, or as an energy storage unit of the device. The device includes but is not limited to mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.

[0068] The device can select a secondary battery, a battery module or a battery pack according to its usage requirements.

[0069] Figure 6 A schematic diagram of a device according to a specific embodiment of the present application is shown. The device may be a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. In order to meet the device's requirements for high power and high energy density of a lithium-ion secondary battery (i.e., the secondary battery of the present application), a battery pack or a battery module may be used.

[0070] As another example, the device may be a mobile phone, a tablet computer, a notebook computer, etc. The device is usually required to be light and thin, and a lithium-ion secondary battery (ie, the secondary battery of the present application) may be used as a power source.

[0071] Those skilled in the art will appreciate that the various limitations or preferred ranges for component selection, component content, and material physical and chemical performance parameters of the electrode sheet, electrode active material layer, etc. in the different embodiments of the present application mentioned above can be arbitrarily combined, and the various embodiments obtained by combining them are still within the scope of the present application and are deemed to be part of the disclosure of this specification.

[0072] Unless otherwise specified, the various parameters involved in this specification have common meanings known in the art and can be measured by methods known in the art. For example, the method provided in the examples of the present application can be used for testing. In addition, the preferred ranges and options of the various parameters provided in the various preferred embodiments can be combined arbitrarily, and the various combinations obtained are considered to be within the scope of the disclosure of the present application.

[0073] The present application is further described below in conjunction with specific examples and comparative examples. It should be understood that these examples are only used to illustrate the present application and are not used to limit the scope of the present application.

[0074] Example

[0075] The preparation method of the positive electrode active material in each example and comparative example is as follows.

[0076] 1. Preparation of positive electrode active materials

[0077] The first positive electrode active material and the second positive electrode active material are mixed in a solvent N-dimethylpyrrolidone (NMP) according to a molar percentage ratio to obtain a mixed slurry with a viscosity of 3000mPa·s to 20000mPa·s. The mixed slurry is allowed to stand for 24 to 48 hours to obtain a positive electrode active material slurry that does not gel, stratify, or settle.

[0078] 2. Preparation of positive electrode sheet

[0079] The positive electrode active material, conductive carbon and binder polyvinylidene fluoride (PVDF) are fully stirred and mixed in a proper amount of N-methylpyrrolidone (abbreviated as NMP) solvent at a weight ratio of 95:3:2 to form a uniform positive electrode slurry; the slurry is coated on the positive electrode current collector Al foil, and after drying, the electrode sheet is cold pressed to the designed density, and separated into strips for standby use to obtain the positive electrode sheet.

[0080] 3. Preparation of electrolyte

[0081] An equal volume of ethylene carbonate is dissolved in propylene carbonate, and then an appropriate amount of lithium hexafluorophosphate is uniformly dissolved in the mixed solvent for later use to obtain an electrolyte.

[0082] 4. Preparation of negative electrode sheet

[0083] The negative electrode active material graphite and conductive carbon, binder polyvinylidene fluoride (PVDF) are fully stirred and mixed in a proper amount of water solvent at a weight ratio of 95:3:2 to form a uniform negative electrode slurry; the slurry is coated on the negative electrode current collector Cu foil, and after drying, the electrode is cold pressed to the designed density and divided into strips for standby use.

[0084] 5. Provide isolation film

[0085] PE film is selected as the isolation film.

[0086] 6. Prepare the battery

[0087] Through the conventional battery manufacturing process, the positive electrode sheet (compacted density: 3.4g / cm 3 ), separator and negative electrode sheet (compacted density: 1.6g / cm 3 ) are wound together into a bare cell, which is then placed in a battery casing, injected with electrolyte, and then sealed and formed to finally obtain a lithium-ion secondary battery (hereinafter referred to as a battery).

[0088] Test Method

[0089] 1) Test method for lithium ion diffusion coefficient of positive electrode sheet and positive electrode active material

[0090] It can be tested by conventional methods in the art such as CV method, EIS method, GITT method, PITT method, etc., and calculated according to Fick's first and second laws.

[0091] Taking the GITT method as an example, the steps for testing the lithium ion diffusion coefficient of the first positive electrode active material or the second positive electrode active material are as follows:

[0092] Grind the first positive electrode active material or the second positive electrode active material into a powder microelectrode; connect the powder microelectrode to the electrochemical workstation and perform coulometric titration. The pulse current is 20μA, the titration time is 1h, and the interval is 4h. (Note: To compare the effects of pulse current and time, a parallel experiment of 10μA and 10min can be performed). After obtaining the GITT curve, the lithium ion diffusion coefficient is calculated using the following formula:

[0093]

[0094] Where D is the lithium ion diffusion coefficient; I0 ​​is the applied current 20 μA; Vm is the molar volume of the active material; F is the Faraday constant; A is the electrode surface area, dE / dx is the slope of the coulomb titration curve, that is, the slope of the open circuit potential at a certain concentration on the Li concentration curve in the electrode; (dE) / (dt 1 / 2 ) is the polarization voltage versus t 1 / 2 The slope of the curve. For details, please refer to the following literature: Xie et al., Solid State Ionics, 2007, 178: 1218–1224; Yang et al., Electrochimica Acta, 2012, 66: 88–93.

[0095] 2) Test method for resistance of positive electrode

[0096] The resistance of the positive electrode piece is measured by using the Hioki BT3562 internal resistance tester, including: clamping the positive electrode piece between two conductive terminals of the internal resistance tester, applying pressure to fix it, and testing the resistance R of the positive electrode piece, wherein the diameter of the conductive terminal is 14 mm, the applied pressure is 15 MPa to 27 MPa, and the sampling time ranges from 5 s to 17 s.

[0097] 3) Powder resistivity test method of positive electrode active material at 20MPa

[0098] The positive electrode active material powder is dried, and an appropriate amount of powder is weighed, and then a powder resistivity tester is used, the equipment model is Suzhou Jingge ST2722 or Sansi Zongheng UTM7305. The dry powder sample is placed in the mold / sample bin of the resistivity tester, the sample bin depth is 20mm, and the cross-sectional area is 1cm2, and then pressure is slowly applied from small to large, and data is manually collected, and the corresponding powder resistivity test results at different pressure points are recorded.

[0099] 4) Testing method of first positive electrode active material I(003) / I(110) and lattice parameter c / a

[0100] Measuring instrument: X-ray powder diffractometer; equipment model: BruckerD8A_A25 from Brucker AxS, Germany. Monochromatic X-rays are used to irradiate polycrystalline samples, and different orientations of the crystals are used to change θ to satisfy the Bragg equation to generate diffraction peaks. The generated diffraction peaks are used to qualitatively analyze the crystal structure and calculate the lattice parameters. For example, CuKα rays are used as the radiation source, and the wavelength of the rays is The scanning 2θ angle range is 10° to 150°, and the scanning rate is 4° / min. After obtaining the diffraction pattern of the powder, it is compared with the diffraction spectrum in the existing crystal database, such as the PDF database, to obtain the crystalline phase corresponding to the material and the crystal plane corresponding to each peak. Then, according to calculation or simulation using crystal structure simulation software, for example, the a-axis and c-axis of the material can be calculated according to the hexagonal crystal system formula 1 / d2=4(h2+hk+k2) / 3a2+l2 / c2, and the (003) and (110) peak intensity integral ratios are calculated to obtain I003 / I110, and the length ratio of the c-axis to the a-axis is c / a.

[0101] 5) Testing method for average particle size of the second positive electrode active material

[0102] Measuring instrument: laser particle size analyzer; equipment model: Malvern Mastersizer 2000E or Mastersizer 3000. Because the angle of scattered light of the particles of the positive electrode material is inversely proportional to the diameter of the particles under the irradiation of the laser beam, and the scattered light intensity decays logarithmically with the increase of the angle, the energy distribution of the scattered light is directly related to the distribution of the particle diameter. By receiving and measuring the energy distribution of the scattered light, the particle size distribution characteristics of the particles can be obtained. The solvent used for the test can be water or other organic solvents used to prepare the slurry, and the sample is dispersed by ultrasound. The obtained analysis result Dv 50 That is, 50% of the particles in the total volume have a diameter greater than this value, and another 50% of the particles in the total volume have a diameter less than this value. 50 To indicate the median particle size of the powder.

[0103] 6) Method for determining the mass percentage of carbon coating of the second positive electrode active material

[0104] Measuring instrument: C / S content analyzer; equipment model: Dekai HCS-140. According to the determination of total carbon and sulfur content of steel, the infrared absorption method after combustion in a high-frequency induction furnace (conventional method) GBT 20123-2006 is used to test the carbon content in the powder. The sample is burned in oxygen to convert carbon and sulfur into CO2 and SO2, which are converted into corresponding signals by the detector after entering the absorption cell. This signal is sampled by a computer, converted into a value proportional to the concentration of CO2 and SO2 after linear correction, and then the values ​​of the entire analysis process are accumulated. After the analysis is completed, this accumulated value is divided by the weight value in the computer, multiplied by the correction coefficient, and the blank is subtracted to obtain the percentage of carbon and sulfur in the sample.

[0105] 7) Positive electrode R d , R ct , R cat Test Method

[0106] R cat ,、R d ,、R ct EIS testing and fitting can be performed by assembling a symmetrical battery with positive electrode pieces and using an electrochemical workstation. The EIS test obtains an AC impedance spectrum, and the impedance composition is deeply analyzed in combination with the equivalent circuit diagram and the impedance decomposition model to obtain the Nyquist diagram and the Bode diagram, which are then fitted using Z-view or EC-Lab software. The overlap between the simulated diagram and the measured diagram is then improved by adjusting the values ​​of each impedance. The higher the overlap, the more accurate the impedance result.

[0107] 8) Lithium-ion battery 273K capacity retention rate test method

[0108] Select fresh battery cells, use a battery charger and discharge machine + high and low temperature box, test the battery's standard rate discharge capacity at a specified temperature, and the ratio of discharge capacity to charge capacity is the capacity retention rate. For relevant terms and test methods, refer to GB / T 19596 and GB / T 31486.

[0109] 9) Lithium-ion battery 253K power @ 5% SOC test method

[0110] Select fresh battery cells, use a battery charger and discharger + high and low temperature box, and test the power performance of the battery at a specified temperature and SOC. For relevant terms and test methods, refer to GB / T 19596 and GB / T 31486.

[0111] Test Results and Discussion

[0112] The specific parameters of the electrochemical performance of the positive electrode active materials, positive electrode sheets and lithium ion secondary batteries of Examples 1 to 9 and Comparative Examples 1 to 2 are shown in Tables 1 to 4.

[0113] Table 1 Parameters of the first positive electrode active material

[0114]

[0115] Table 2 Parameters of the second positive electrode active material

[0116]

[0117] Table 3 Performance parameters of positive electrode active materials and positive electrode sheets

[0118]

[0119] Table 4 Electrochemical performance of lithium-ion batteries

[0120] 273K capacity retention rate 253K Power @ 5% SOC [W] Example 1 92% 212 Example 2 91% 207 Example 3 90% 198 Example 4 90% 172 Example 5 91% 159 Example 6 92% 205 Example 7 93% 187 Example 8 93% 167 Example 9 93% 191 Comparative Example 1 66% 47 Comparative Example 2 60% 39

[0121] From the analysis of the data in Tables 1 to 4, it can be seen that, compared with Comparative Examples 1 and 2, Examples 1 to 9 use a first positive electrode active material and a second positive electrode active material with different working voltage platforms, and the charge and discharge platforms of the two positive electrode active materials are complementary and synergistic, so that the ion conductivity and the electronic conductivity of the electrode sheet are better matched, and the lithium ion solid phase diffusion coefficient and resistance of the positive electrode sheet are both within a better range, and the rate performance of the lithium ion secondary battery at low temperature and low SOC is significantly improved. In addition, on the basis of making the charge and discharge platforms of the two positive electrode active materials complementary, the present application further improves the conductivity, crystallinity and order of the positive electrode active material from the aspects of the lithium ion solid phase diffusion coefficient, powder resistivity, particle morphology, particle size and carbon coating amount, and X-ray diffraction spectrum key parameters of the selected first positive electrode active material and the second positive electrode active material, thereby improving the dynamics and charge and discharge performance of the battery. The power performance of the secondary battery provided by the present application at low temperature and low SOC is significantly higher than that of the secondary battery prepared by a single positive electrode active material.

[0122] Those skilled in the art can understand that the above only uses lithium batteries as an example to illustrate the application examples of the pole pieces of the present application, but the pole pieces of the present application can also be applied to other types of batteries or secondary batteries, and still achieve the good technical effects of the present application.

[0123] According to the disclosure and teaching of the above description, the technical personnel in the field to which the present application belongs can also make appropriate changes and modifications to the above implementation. Therefore, the present application is not limited to the specific implementation methods disclosed and described above, and some modifications and changes to the present application should also fall within the scope of protection of the claims of the present application. In addition, although some specific terms are used in this specification, these terms are only for the convenience of explanation and do not constitute any limitation to the present application.

Claims

1. A secondary battery, comprising a positive electrode sheet, wherein the positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer, wherein the positive electrode active material layer is located on the surface of the positive electrode current collector, characterized in that: The positive electrode active material layer includes a first positive electrode active material and a second positive electrode active material having different operating voltage platforms; The lithium ion solid phase diffusion coefficient of the positive electrode plate is 10 -17 cm 2 ·s -1 ~10 -5 cm 2 ·s -1 ; The resistance of the positive electrode plate is 0.05Ω to 2Ω.

2. The secondary battery according to claim 1, characterized in that: The lithium ion solid phase diffusion coefficient of the positive electrode plate is 10 -13 cm 2 ·s -1 ~10 -9 cm 2 ·s -1 .

3. The secondary battery according to claim 1, characterized in that: The resistance of the positive electrode plate is 0.1Ω to 1.5Ω.

4. The secondary battery according to claim 1, characterized in that: The first positive electrode active material is selected from layered lithium nickel transition metal oxides.

5. The secondary battery according to claim 4, characterized in that: The layered lithium nickel transition metal oxide is selected from: Li x1 Ni (1-y1-z1-a1) Co y1 Mn z1 M1 a1 O2、Lix2Ni (1-y2-z2-a2) Co y2 Al z2 M2 a2 O2, and one or more of the composite materials obtained by coating and modification of the above materials; Among them, 0.90≤x1≤1.05, 0<y1≤0.2, 0<z1≤0.2, 0≤a1≤0.05, M1 is selected from one or more of Ti, Al, Zr, Mg, Zn, Ba, Mo, and B; 0.90≤x2≤1.05, 0<y2≤0.1, 0<z2≤0.1, 0≤a2≤0.05, M2 is selected from one or more of Ti, Mn, Zr, Mg, Zn, Ba, Mo, and B.

6. The secondary battery according to claim 5, characterized in that: 0<y1+z1+a1≤0.4; 0<y2+z2+a2≤0.

4.

7. The secondary battery according to claim 1, characterized in that: The second positive electrode active material is selected from olivine-type lithium-containing phosphates.

8. The secondary battery according to claim 7, characterized in that: The olivine-type lithium-containing phosphate is LiFe 1-x3- y3 Mn x3 M' y3 PO4, wherein 0≤x3≤1, 0≤y3≤0.1, 0≤x3+y3≤1, and M' is selected from one or more of transition metal elements and non-transition metal elements except Fe and Mn.

9. The secondary battery according to claim 7, characterized in that: The olivine-type lithium-containing phosphate is selected from the group consisting of doped and modified LiFePO4, LiMnPO4, LiMn 1-x4 Fe x4 One or more of PO4, where 0<x4<1.

10. The secondary battery according to claim 1, characterized in that: The lithium ion solid phase diffusion coefficient of the first positive electrode active material is 10 -13 cm 2 ·s -1 ~10 -7 cm 2 ·s -1 ;and, The powder resistivity of the first positive electrode active material at 20 MPa is 1000 Ω·cm to 20000 Ω·cm.

11. The secondary battery according to claim 10, characterized in that: The lithium ion solid phase diffusion coefficient of the first positive electrode active material is 10 -11 cm 2 ·s -1 ~10 -9 cm 2 ·s -1 .

12. The secondary battery according to claim 10, characterized in that: The powder resistivity of the first positive electrode active material at 20 MPa is 2000 Ω·cm to 10000 Ω·cm.

13. The secondary battery according to claim 10, characterized in that: The powder resistivity of the first positive electrode active material at 20 MPa is 3000 Ω·cm to 6000 Ω·cm.

14. The secondary battery according to claim 1, characterized in that: The lithium ion solid phase diffusion coefficient of the second positive electrode active material is 10 -17 cm 2 ·s -1 ~10 -11 cm 2 ·s -1 ;and, The powder resistivity of the second positive electrode active material at 20 MPa is 10 Ω·cm to 4000 Ω·cm.

15. The secondary battery according to claim 14, characterized in that: The lithium ion solid phase diffusion coefficient of the second positive electrode active material is 10 -16 cm 2 ·s -1 ~10 -13 cm 2 ·s -1 .

16. The secondary battery according to claim 14, characterized in that: The lithium ion solid phase diffusion coefficient of the second positive electrode active material is 10 -15 cm 2 ·s -1 ~10 -14 cm 2 ·s -1 .

17. The secondary battery according to claim 14, characterized in that: The powder resistivity of the second positive electrode active material at 20 MPa is 20 Ω·cm to 800 Ω·cm.

18. The secondary battery according to claim 14, characterized in that: The powder resistivity of the second positive electrode active material at 20 MPa is 200 Ω·cm to 550 Ω·cm.

19. The secondary battery according to claim 1, characterized in that: The molar percentage of the second positive electrode active material to the positive electrode active material is 0.5% to 50%.

20. The secondary battery according to claim 1, characterized in that: The molar percentage of the second positive electrode active material to the positive electrode active material is 0.6% to 30%.

21. The secondary battery according to claim 1, characterized in that: The molar percentage of the second positive electrode active material to the positive electrode active material is 0.7% to 20%.

22. The secondary battery according to claim 1, characterized in that: The particle morphology of the first positive electrode active material is selected from single crystal particles, polycrystalline particles or a mixture thereof.

23. The secondary battery according to claim 1, characterized in that: The particle morphology of the first positive electrode active material is selected from single crystal particles.

24. The secondary battery according to claim 1, characterized in that: The I003 / I110 in the X-ray diffraction spectrum of the first positive electrode active material is 2 to 20; and / or, The lattice parameter c / a of the first positive electrode active material in an X-ray diffraction spectrum is 2-7.

25. The secondary battery according to claim 24, characterized in that: The I003 / I110 in the X-ray diffraction spectrum of the first positive electrode active material is 4-12.

26. The secondary battery according to claim 24, characterized in that: The I003 / I110 in the X-ray diffraction spectrum of the first positive electrode active material is 6-10.

27. The secondary battery according to claim 24, characterized in that: The lattice parameter c / a of the first positive electrode active material in an X-ray diffraction spectrum is 3-6.

28. The secondary battery according to claim 1, characterized in that: The average particle size Dv50 of the second positive electrode active material is 1 μm to 15 μm; and / or, The mass percentage of the carbon coating of the second positive electrode active material is 0.1% to 5%.

29. The secondary battery according to claim 28, characterized in that: The average particle size Dv50 of the second positive electrode active material is 4.5 μm to 13.5 μm.

30. The secondary battery according to claim 28, characterized in that The average particle size Dv50 of the second positive electrode active material is 5 μm to 9 μm.

31. The secondary battery according to claim 28, characterized in that: The mass percentage of the carbon coating of the second positive electrode active material is 0.5% to 3%.

32. The secondary battery according to claim 28, characterized in that: The mass percentage of the carbon coating of the second positive electrode active material is 1% to 2%.

33. The secondary battery according to claim 1, characterized in that: The positive electrode sheet satisfies: 0.41<(R d +R ct ) / R cat <0.99, and 0.2<R ct / R d <2; Among them, R cat is the total impedance of the positive electrode, R d is the lithium ion diffusion impedance of the positive electrode plate, R ct is the charge transfer impedance of the positive electrode plate.

34. A device comprising the secondary battery according to any one of claims 1 to 33, wherein the secondary battery is used as a power source of the device or an energy storage unit of the device.

Citation Information

Patent Citations

  • Active material composition for positive electrode, positive electrode slurry and preparation method thereof, positive plate and preparation method thereof, and lithium ion battery

    CN105470494A

  • Lithium ion battery and electric equipment comprising same

    CN110323487A